Hypertonic Cryohemolysis of Mammalian Erythrocytes - Shpakova, N. M.; Ershov, S. S. (Problems of Cryobiology and Cryomedicine, 2006)
Sensitivity of mammalian (human, bovine, equine, canine) erythrocytes to cooling from 37 down to 0Â°C in hypertonic saline solutions has been studied. The obtained experimental results demonstrated hypertonic cryohemolysis as typical not only for human erythrocytes but for bovine, equine, and canine cells as well. Both canine erythrocytes and human cells are maximally damaged in the medium, containing 1.2M and 1.4M NaCl for equine ones, meanwhile for bovine erythrocytes a gradual augmentation of cryohemolysis is observed with growth in medium osmolarity (up to 2.0 M NaCl).